Acute development of Cushing syndrome in an HIV-infected child on atazanavir/ritonavir based antiretroviral therapy. (28th October 2017) - Dubrocq, Gueorgui; Estrada, Andrea; Kelly, Shannon; Rakhmanina, Natella
Summary: An 11-year-old male with perinatally acquired human immune deficiency virus (HIV) infection on antiretroviral regimen, which included abacavir plus lamivudine (Epzicom), didanosine, ritonavir and atazanavir presented with bilateral axillary striae, increased appetite, fatigue, facial swelling and acute weight gain. Two months prior to presentation, the patient had received a diagnostic and therapeutic intra-articular triamcinolone injection in the knee for pain relief and subsequently became progressively swollen in the face, developed striae bilaterally at the axillae, experienced increased appetite, fatigue and an 8 pound weight gain. During the endocrine workup, suspicion for adrenal insufficiency prompted 24-h urine collection for free cortisol, which was found to be undetectable (below LLQ of 1.0 µg/L). This prompted further evaluation of the hypothalamic–pituitary axis (HPA) by standard dose adrenocorticotropic hormone (ACTH) stimulation test. A 250 µg cosyntropin stimulation test was performed and confirmed HPA axis suppression. Baseline cortisol level was <1 µg/dL and stimulated cortisol level at 30 min was 3.8 µg/dL. The patient was diagnosed with iatrogenic Cushing syndrome and suppression of HPA axis secondary to the drug interaction between ritonavir (RTV) and intra-articular triamcinolone injection. Following endocrine evaluation and workup, the patient was admitted for planned orthopaedic procedure including elective left hamstring lengthening, distal femoral osteotomy and patellar tendon advancement. Taking into consideration the diagnosis of iatrogenic Cushing syndrome, at the start of the surgical procedure, 100 mg IV stress dose of hydrocortisone followed by 50 mg hydrocortisone every 8 h for 24 h was administered. Stress dosing was discontinued 24 h after the procedure. Throughout the hospitalization and upon discharge, the patient continued his ART. From initial presentation, patient has remained clinically stable throughout surgery and postoperative period. Learning points: Drug–drug interaction between ritonavir and triamcinolone can cause Cushing syndrome. Although triamcinolone has a half-life of 3 h, an intra-articular injection may be systematically absorbed for 3 weeks after injection, and adrenal suppression may last as long as 30 days. Co-administration of ritonavir and corticosteroids may result in an increase of plasma levels of corticosteroids levels, as they are both eliminated by CYP3A metabolism, and this interaction has the potential to prolong the half-life of triamcinolone several fold. No specific guidelines are available for the management of iatrogenic Cushing syndrome secondary to ritonavir and corticosteroids. One treatment option includes replacing ritonavir with a non-protease inhibitor-based regimen. Initiating hydrocortisone replacement therapy to prevent an adrenal crisis is also an alternate option.